Changes in Radial Polyp Tissues of Acropora Longicyathus After Long-Term Exposure to Experimentally Elevated Nutrient Concentrations - Bucher, Daniel J.; Harrison, Peter L. (Frontiers in Marine Science, 2018)
Coral tissues control growth and calcification processes that ultimately build coral reefs but relatively little information is available on the effects of nutrients on polyp tissues. The structure and organisation of coral tissues were investigated using thin (0.5–1µm) sections of young (<3 months) radial polyps of the reef-building coral Acropora longicyathus that had been exposed to elevated concentrations of ammonium (‘N’) and/or phosphate (‘P’) in the ENCORE experiment at One Tree Island, southern Great Barrier Reef. Young polyps of N-treated corals had similar porosity but significantly decreased length of calicoblastic body wall per cross-section of the septotheca compared with controls. Other studies using older skeletons of the same corals found they were significantly less porous than controls and their branches had reduced extension rates and reduced lesion-healing ability, indicating that increased calcification occurred in the infilling process rather than during apical extension. The free body wall epidermal tissues of P-treated polyps were significantly thicker than corals in control conditions and their calyx walls had significantly greater length of calicoblastic body wall per cross-section despite similar porosity to controls. This suggests that phosphate stimulated tissue growth and apical calcification. Although other studies of the chlorophyll content of older tissue found it was significantly increased by phosphate treatments, more rapid extension of the branches kept Symbiodiniacean densities in the younger polyps similar to controls. We recorded a reduction in the density of mucous bodies in P-treated corals, which is potentially significant for the survival of corals in polluted water because of the important roles of mucus in facilitating removal of sediment from the coral surface and as a barrier to pathogen infection.